Diabetic Foot Ulcer Prevention: An Evidence Based Practice - Kharisma Pratama; Nichapatr Phuttikhamin (Sekolah Tinggi Ilmu Keperawatan Muhammadiyah Pontianak, 2017)
Background: Diabetic foot ulcer (DFU) is one of diabetes mellitus complication that increases from year by year. There was 15% diabetes mellitus patients suffered DFU and around 50% DFU patients die within five years. This study aimed to develop the guidelines for preventing diabetic foot ulcer. Data collection was carried out from March to April 2017. There were 40 nurses included in this study which are working at IPD of city hospital in Pontianak, West Borneo, Indonesia. Methods: Tools for data collection included guideline for DFU prevention and guideline manual for nurses, while tools for outcome evaluation included Nursing competency for DFU prevention form, Nurse Opinion Questionnaire and Nurse Agreement on Guideline. The content validity of the Nurse Opinion Questionnaire was 1.0 and Nursing Competency for DFU prevention was 1.0. The internal consistency of Nurse Agreement on Guideline using Cronbach’s alpha was 0.89. Data analysis was performed using descriptive statistics. Results: The guidelines of DFU prevention in DM patients who admitted into the hospital has been developed, and most nurses provided the expected response. Some nurses agreed and highly agreed with the guidelines. Conclusions: The guidelines of DFU prevention are useful and important for nursing practice. Nurses can use the guidelines to protect and prevent their DM patient from diabetic foot ulcer or infection. In addition, some recommendations for nursing practice and further study were proposed.